Aplicação da técnica de caminhamento elétrico em area contaminada por derivados de petróleo - Moreira, César Augusto [UNESP]; Dourado, João Carlos [UNESP]; De Oliveira Braga, Antonio Celso [UNESP] (My University, 2006)
Geophysical methods are useful technics of geological investigation, thoroughly employed to diagnosis and monitoring contaminated areas, in conjunction with direct techniques of investigation such as chemical analyses. Among these, electric resistivity is more usually used in studies of contaminants in soil and groundwater, due to the high contrast of electric properties between the soil and the pollutant types frequently found, essentially constituted of composed organic and inorganic, Geophysical studies in impacted areas by petroleum products may be describe by anomalies of both low resistivity and high resistivities, confirmed as contaminant by chemical analyses. This apparent contradiction can reflect processes of degradation of the contaminants, directly associated with its residence time in the soil, through the generation of by-products that change the physical properties of the soil and groundwater, principally for the mineral dissolution by action of organic acids and by formation of minerals of oxides and hydroxides minerals. Natural attenuation defines a series of physical, chemical and biological processes that allow the degradation, dispersion and dilution of contaminants in a natural form, in other words, free from human intervention. This paper presents the application of electrical profiling technique in a contaminated industrial area for benzene, toluene, xylene, 1,2 dichloroethene and inorganic salts and it discusses the physical alterations of the contaminated soil through the obtained results, under the optics of the Natural Attenuation in course in the area of study. ©2006 Sociedade Brasileira de Geofísica.
Application of the technique of electrical profiling in the area contaminated by petroleum products
Keywords: Biodegradation; Electric resistivity; Electrical profiling; NAPL; Natural attenuation